End-to-end approach for the characterization and control of product-related impurities in T cell bispecific antibody preparations - Laurent Larivière; Julia Eva Krüger; Thomas von Hirschheydt; Tilman Schlothauer; Katharine Bray-French; Martin Bader; Valeria Runza (Elsevier, 2023)
Antibody-based T cell-activating biologics are promising therapeutic medicines being developed for a number of indications, mainly in the oncology field. Among those, T cell bispecific antibodies are designed to bind one tumor-specific antigen and the T cell receptor at the same time, leading to a robust T cell response against the tumor. Although their unique format and the versatility of the CrossMab technology allows for the generation of safer molecules in an efficient manner, product-related variants cannot be completely avoided. Therefore, it is of extreme importance that both a manufacturing process that limits or depletes product-related impurities, as well as a thorough analytical characterization are in place, starting from the development of the manufacturing cell line until the assessment of potential toxicities. Here, we describe such an end-to-end approach to minimize, quantify and control impurities and -upon their functional characterization- derive specifications that allow for the release of clinical material.